Green Banking and Sustainability Disclosures in the Islamic Banking Sector: Evidence from Malaysia - Muhammad Zuki, Mohd Faizuddin; Ishak, Muhammad Arif Fadilah; Muhammad Hafiz, Hassan (Organizations and Markets in Emerging Economies, 2026)
The heightened global focus on sustainability has intensified expectations for financial institutions, including Islamic banks, to embed green finance and sustainable practices within their operations. Although Malaysia remains a global leader in Islamic finance, questions persist regarding the depth of sustainability implementation beyond narrative disclosure. This study examines the extent to which full-fledged Islamic banks in Malaysia operationalize green finance and sustainability principles, and evaluates their alignment with national and global frameworks. A qualitative exploratory design was employed, incorporating systematic content analysis and thematic review of sustainability, annual, and integrated reports from six Islamic commercial and development banks. To enhance rigor, a triangulation strategy validated findings against academic literature, regulatory documents, and institutional policy sources. In addition, a quantitative content analysis was conducted through a structured 0–4 scoring rubric applied across fifteen indicators, generating a Green Banking and Sustainability Index (GBSI) scaled to 0–100. The results reveal four emerging themes–climate risk management, compliance with sustainability frameworks, environmental footprint reduction, and green financing activities, with banks demonstrating varying maturity across initiatives. GBSI scores ranged from 40.3 to 66.7, indicating moderate progress yet uneven adoption across institutions. Positive strides were noted in energy efficiency, digitalisation, and initial climate-disclosure efforts, while gaps remain in renewable energy deployment, green procurement, verified performance metrics, and standardised reporting. This study contributes empirical insight into ESG integration within Islamic banking, advances legitimacy theory and provides actionable recommendations to strengthen execution consistency, enhance reporting quality, and support Malaysia’s strategic ambition in Islamic green finance.